Microbial community changes at a terrestrial volcanic CO2 vent induced by soil acidification and anaerobic microhabitats within the soil column. Issue 1 (10th December 2012) - Frerichs, Janin; Oppermann, Birte I.; Gwosdz, Simone; Möller, Ingo; Herrmann, Martina; Krüger, Martin
Abstract: CO2 capture and storage (CCS) in deep geological formations is one option currently evaluated to reduce greenhouse gas emissions. Consequently, the impact of a possible CO2 leakage from a storage site into surface environments has to be evaluated. During such a hypothetical leakage event, the CO2 migrates upwards along fractures entering surface soils, a scenario similar to naturally occurring CO2 vents. Therefore, such a natural analogue site at the Laacher See was chosen for an ecosystem study on the effects of high CO2 concentrations on soil chemistry and microbiology. The microbial activities revealed differences in their spatial distribution and temporal variability for CO2 ‐rich and reference soils. Furthermore, the abundance of several functional and group‐specific gene markers revealed further differences, for example, a decrease in Geobacteraceae and an increase in sulphate‐reducing prokaryotes in the vent centre. Molecular–biological fingerprinting of the microbial communities with DGGE indicated a shift in the environmental conditions within the Laacher See soil column leading to anaerobic and potentially acidic microenvironments. Furthermore, the distribution and phylogenetic affiliation of the archaeal 16S rRNA genes, the presence of ammonia‐oxidizing Archaea and the biomarker analysis revealed a predominance of Thaumarchaeota as possible indicator organisms for elevated CO2 concentrations in soils.